2022
DOI: 10.1029/2021jd036059
|View full text |Cite
|
Sign up to set email alerts
|

Highly Active Ice‐Nucleating Particles at the Summer North Pole

Abstract: The amount of ice versus supercooled water in clouds is important for their radiative properties and role in climate feedbacks. Hence, knowledge of the concentration of ice‐nucleating particles (INPs) is needed. Generally, the concentrations of INPs are found to be very low in remote marine locations allowing cloud water to persist in a supercooled state. We had expected the concentrations of INPs at the North Pole to be very low given the distance from open ocean and terrestrial sources coupled with effective… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 108 publications
2
22
0
Order By: Relevance
“…However, clouds in the summertime Arctic are normally mixed-phase 89 (consisting of both water droplets and ice), which was also the case during most of our expedition. 45 Measured INP 48 concentrations between September 11 and September 19 were however relatively low and exhibited a low ice-nucleating ability (freezing temperature at 0.1 INP L –1 was around −25 to −30 °C). This indicates that the clouds were largely composed of liquid droplets and that κ -Köhler theory can be used to predict the cloud activation, which simplifies the description of the aerosol–cloud interactions.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, clouds in the summertime Arctic are normally mixed-phase 89 (consisting of both water droplets and ice), which was also the case during most of our expedition. 45 Measured INP 48 concentrations between September 11 and September 19 were however relatively low and exhibited a low ice-nucleating ability (freezing temperature at 0.1 INP L –1 was around −25 to −30 °C). This indicates that the clouds were largely composed of liquid droplets and that κ -Köhler theory can be used to predict the cloud activation, which simplifies the description of the aerosol–cloud interactions.…”
Section: Resultsmentioning
confidence: 99%
“…The geographical locations for the scientific activities ranged from the marginal ice zone (MIZ, ∼82° N) north of Svalbard to close to the North Pole (89° N), where the icebreaker was moored and drifting for nearly 5 weeks. The general goal of MOCCHA was to investigate potential links between marine microbiology, local aerosol emissions, and cloud formation in the central Arctic Ocean. ,, …”
Section: Methodsmentioning
confidence: 98%
See 1 more Smart Citation
“…However, recently Porter et al. ( 2022 ) found that the most active INP in the central Arctic could be traced back to the waters and coasts of Siberia, while local sources in the pack ice and marginal ice zone were less important.…”
Section: Introductionmentioning
confidence: 99%
“…In the summertime high Arctic, the limited influence of long-range transport means more local sources may also be important Leck & Svensson, 2015). However, recently Porter et al (2022) found that the most active INP in the central Arctic could be traced back to the waters and coasts of Siberia, while local sources in the pack ice and marginal ice zone were less important.…”
mentioning
confidence: 99%